Outcome Comparison of 600 mg versus 300 mg Loading dose of Clopidogrel for Patients with ST-Elevation Myocardial Infarction: A Meta-Analysis. Issue 5 (September 2014) - Vyas, Ankur; Accaoui, Ramzi El; Blevins, Amy; Karrowni, Wassef
Abstract: Background: A 600-mg loading dose (LD) of clopidogrel has been shown to be superior to a 300-mg LD in inhibiting platelet function. However, data for clinical superiority are limited, and there is a paucity of adequately powered randomized trials investigating this issue. This meta-analysis was performed to determine the optimal LD of clopidogrel in ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention.Methods: A meta-analysis of controlled trials and observational studies was performed comparing 600-mg with 300-mg LDs of clopidogrel. The primary efficacy end point was a major adverse cardiac event (MACE), and the primary safety end point was major bleeding. Data were extracted on an intention to treat basis. The X 2 test was used to evaluate heterogeneity. A random effects model was used, and odds ratios (OR) were calculated using the Mantel-Haenszel method.Results: Nine studies involving 18 623 patients were included in the efficacy analysis. Mean duration of follow-up was 8 months. Four studies were eligible for the safety analysis. The MACE risk was lower with a 600-mg LD (7.0% [650/9231]) than with a 300-mg LD (9.2% [867/9392]; OR, 0.75; 95% CI, 0.63-0.91). On the other hand, there was no significant difference in the major bleeding events between the 2 groups (2.5% [89/3551] with 600 mg vs 2.3% [63/2796] with 300 mg; OR, 0.84; 95% CI, (0.60-1.16).Conclusions: In ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention, administration of a 600-mg LD of clopidogrel is associated with a lower risk of MACE than is administration of a 300-mg LD, without increasing the risk of major bleeding.